Seeing the conflict: an attentional account of reasoning errors - Mata, André; Ferreira, Mário B.; Voß, Andreas (Psychonomic bulletin & review, 2017)
In judgment and reasoning, intuition and deliberation can agree on the same responses, or they can be in conflict and suggest different responses. Incorrect responses to conflict problems have traditionally been interpreted as a sign of faulty problem-solving—an inability to solve the conflict. However, such errors might emerge earlier, from insufficient attention to the conflict. To test this attentional hypothesis, we manipulated the conflict in reasoning problems and used eye-tracking to measure attention. Across several measures, correct responders paid more attention than incorrect responders to conflict problems, and they discriminated between conflict and no-conflict problems better than incorrect responders. These results are consistent with a two-stage account of reasoning, whereby sound problem solving in the second stage can only lead to accurate responses when sufficient attention is paid in the first stage.